Guided wave optical components and devices : basics, technology, and applications - Pal, Bishnu P., 1948- (Optics and photonics., 2006)
The book provides a comprehensive, lucid, and clear introduction to the world of guided wave optical components and devices. Bishnu Pal has collaborated with some of the greatest minds in optics to create a truly inclusive treatise on this contemporary topic. Written by leaders in the field, this book delivers cutting-edge research and essential information for professionals, researchers, and students on emerging topics like microstructured fibers, broadband fibers, polymer fiber components and waveguides, acousto-optic interactions in fibers, higher order mode fibers, nonlinear and parametric process in fibers, revolutionary effects of erbium doped and Raman fiber amplifiers in DWDM and CATV networks, all-fiber network branching component technology platforms like fused fiber couplers, fiber gratings, and side-polished fiber half-couplers, arrayed waveguides, optical MEMS, fiber sensing technologies including safety, civil structural health monitoring, and gyroscope applications. * Accessible introduction to wide range of topics relating to established and emerging optical components. * Single-source reference for graduate students in optical engineering and newcomer practitioners, focused on components. * Extensive bibliographical information included so readers can get a broad introduction to a variety of optical components and their applications in an optical network.